The Implementation of National Health Insurance in Manusak Village - Pellondou, Indri; Ragaletha, Tadeus A. L.; Limbu, Ribka; Kenjam, Yoseph (Timorese Journal of Public Health, 2021)
Health insurance is a guarantee in the form of health protection so that participants get health care benefits and protection in meeting basic health needs that are given to everyone who has paid the Health Insurance Contribution or the Health Insurance Contibution is paid by the Central Government or Regional Government. That study aims to determine the implementation of the National Health Insurance (JKN) in Manusak Village, East Kupang District, Kupang Regency. The population and sample of this study were 41 people who were JKN Mandiri participants in Manusak Village. Sample was done by sampling technique. Data analysis was carried oit by univariate analysis of each research variable. The results showed that most respondents did not want to pay BPJS contributions if the contributions were insurezsed (70.7%), who were willing to pay BPJS contributions if the fees were lowered (51.2%), and there were respondents who had never paid BPJS contributions (53,7%). Most of the JKN Mandiri participants were unable to pay premiums anymore, namely as many as 22 respondents (53.7%) and as many as 19 respondents (46.3%) who were still able to pay premiums. The conclusion of this study is that most of the JKN Mandiri participants in Manusak Village do not want to pay dues anymore and most of them do not have the ability to pay the dues anymore, while with regard to access to health services, the community does not experience problems related to access to health services